Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To find the value of [tex]\( a^2 + \frac{1}{a^2} \)[/tex] for the quadratic equation [tex]\( a^2 - 6a + 1 = 0 \)[/tex]:
1. Identify the given quadratic equation: [tex]\( a^2 - 6a + 1 = 0 \)[/tex].
2. Use the quadratic formula to solve for [tex]\( a \)[/tex]:
The quadratic formula is:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, comparing [tex]\( a^2 - 6a + 1 = 0 \)[/tex] with [tex]\( ax^2 + bx + c = 0 \)[/tex], we have:
[tex]\[ a = 1, \quad b = -6, \quad c = 1 \][/tex]
3. Calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac = (-6)^2 - 4(1)(1) = 36 - 4 = 32 \][/tex]
4. Find the roots using the quadratic formula:
[tex]\[ a = \frac{-(-6) \pm \sqrt{32}}{2(1)} = \frac{6 \pm \sqrt{32}}{2} = \frac{6 \pm 4\sqrt{2}}{2} = 3 \pm 2\sqrt{2} \][/tex]
Therefore, the two roots are:
[tex]\[ a_1 = 3 + 2\sqrt{2} \quad \text{and} \quad a_2 = 3 - 2\sqrt{2} \][/tex]
5. Calculate [tex]\( a^2 + \frac{1}{a^2} \)[/tex] for each root:
For [tex]\( a_1 = 3 + 2\sqrt{2} \)[/tex]:
[tex]\[ a_1^2 = (3 + 2\sqrt{2})^2 = 9 + 12\sqrt{2} + 8 = 17 + 12\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_1} = \frac{1}{3 + 2\sqrt{2}} = \frac{1}{3 + 2\sqrt{2}} \times \frac{3 - 2\sqrt{2}}{3 - 2\sqrt{2}} = \frac{3 - 2\sqrt{2}}{(3 + 2\sqrt{2})(3 - 2\sqrt{2})} = \frac{3 - 2\sqrt{2}}{9 - 8} = 3 - 2\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_1^2} = (3 - 2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
[tex]\[ a_1^2 + \frac{1}{a_1^2} = (17 + 12\sqrt{2}) + (17 - 12\sqrt{2}) = 34 \][/tex]
Similarly, for [tex]\( a_2 = 3 - 2\sqrt{2} \)[/tex]:
[tex]\[ a_2^2 = (3 - 2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_2} = \frac{1}{3 - 2\sqrt{2}} = \frac{1}{3 - 2\sqrt{2}} \times \frac{3 + 2\sqrt{2}}{3 + 2\sqrt{2}} = \frac{3 + 2\sqrt{2}}{(3 - 2\sqrt{2})(3 + 2\sqrt{2})} = \frac{3 + 2\sqrt{2}}{9 - 8} = 3 + 2\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_2^2} = (3 + 2\sqrt{2})^2 = 9 + 12\sqrt{2} + 8 = 17 + 12\sqrt{2} \][/tex]
[tex]\[ a_2^2 + \frac{1}{a_2^2} = (17 - 12\sqrt{2}) + (17 + 12\sqrt{2}) = 34 \][/tex]
Hence, the value of [tex]\( a^2 + \frac{1}{a^2} \)[/tex] for both roots is [tex]\( 34 \)[/tex].
1. Identify the given quadratic equation: [tex]\( a^2 - 6a + 1 = 0 \)[/tex].
2. Use the quadratic formula to solve for [tex]\( a \)[/tex]:
The quadratic formula is:
[tex]\[ a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, comparing [tex]\( a^2 - 6a + 1 = 0 \)[/tex] with [tex]\( ax^2 + bx + c = 0 \)[/tex], we have:
[tex]\[ a = 1, \quad b = -6, \quad c = 1 \][/tex]
3. Calculate the discriminant:
[tex]\[ \text{Discriminant} = b^2 - 4ac = (-6)^2 - 4(1)(1) = 36 - 4 = 32 \][/tex]
4. Find the roots using the quadratic formula:
[tex]\[ a = \frac{-(-6) \pm \sqrt{32}}{2(1)} = \frac{6 \pm \sqrt{32}}{2} = \frac{6 \pm 4\sqrt{2}}{2} = 3 \pm 2\sqrt{2} \][/tex]
Therefore, the two roots are:
[tex]\[ a_1 = 3 + 2\sqrt{2} \quad \text{and} \quad a_2 = 3 - 2\sqrt{2} \][/tex]
5. Calculate [tex]\( a^2 + \frac{1}{a^2} \)[/tex] for each root:
For [tex]\( a_1 = 3 + 2\sqrt{2} \)[/tex]:
[tex]\[ a_1^2 = (3 + 2\sqrt{2})^2 = 9 + 12\sqrt{2} + 8 = 17 + 12\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_1} = \frac{1}{3 + 2\sqrt{2}} = \frac{1}{3 + 2\sqrt{2}} \times \frac{3 - 2\sqrt{2}}{3 - 2\sqrt{2}} = \frac{3 - 2\sqrt{2}}{(3 + 2\sqrt{2})(3 - 2\sqrt{2})} = \frac{3 - 2\sqrt{2}}{9 - 8} = 3 - 2\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_1^2} = (3 - 2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
[tex]\[ a_1^2 + \frac{1}{a_1^2} = (17 + 12\sqrt{2}) + (17 - 12\sqrt{2}) = 34 \][/tex]
Similarly, for [tex]\( a_2 = 3 - 2\sqrt{2} \)[/tex]:
[tex]\[ a_2^2 = (3 - 2\sqrt{2})^2 = 9 - 12\sqrt{2} + 8 = 17 - 12\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_2} = \frac{1}{3 - 2\sqrt{2}} = \frac{1}{3 - 2\sqrt{2}} \times \frac{3 + 2\sqrt{2}}{3 + 2\sqrt{2}} = \frac{3 + 2\sqrt{2}}{(3 - 2\sqrt{2})(3 + 2\sqrt{2})} = \frac{3 + 2\sqrt{2}}{9 - 8} = 3 + 2\sqrt{2} \][/tex]
[tex]\[ \frac{1}{a_2^2} = (3 + 2\sqrt{2})^2 = 9 + 12\sqrt{2} + 8 = 17 + 12\sqrt{2} \][/tex]
[tex]\[ a_2^2 + \frac{1}{a_2^2} = (17 - 12\sqrt{2}) + (17 + 12\sqrt{2}) = 34 \][/tex]
Hence, the value of [tex]\( a^2 + \frac{1}{a^2} \)[/tex] for both roots is [tex]\( 34 \)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.